Utilization of AI Chatbot for Islamic Integration in Scientific Writing and Islamic Religious Education Learning - Nur Afika Farkhana; Titin Sumarni (Konsultan Jurnal Ilmiah Indonesia, 2026)
The rapid development of Artificial Intelligence (AI) is reshaping education, including Islamic Religious Education (IRE), by enabling learning experiences that are more personalized, interactive, and adaptive. This research explores how AI especially chatbots is applied in IRE teaching and in producing scholarly works grounded in Islamic principles. Using a qualitative literature review approach with Miles and Huberman’s data analysis framework, the study draws primary data from reputable academic journals, supplemented by policy documents and relevant books for triangulation. The results indicate that AI in IRE is implemented through computer-assisted instruction, AI-enhanced online platforms, adaptive media, Islamic-oriented chatbots, and learning analytics. Chatbots have demonstrated the ability to improve learning effectiveness and engagement by tailoring content, delivering instant feedback, and providing asynchronous communication channels that help alleviate students’ academic anxiety. In the context of scientific writing, AI supports literature exploration, structuring arguments, and language refinement, while also being customizable as a virtual ethical guide that upholds academic integrity and ensures the accuracy of Islamic sources. Despite these benefits, several obstacles persist, such as inadequate infrastructure, insufficient digital competence among educators, cultural opposition, algorithmic bias, and ethical concerns including plagiarism and data security. Hence, AI integration in IRE must be anchored in the values of tawhid, trustworthiness, fairness, and balance, alongside Islamic digital literacy, continuous teacher guidance, and clear institutional ethical guidelines. When these conditions are fulfilled, AI can serve as a powerful driver to advance Islamic education that is both progressive and rooted in adab.